2019
DOI: 10.1111/febs.14786
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial metabolism is inhibited by the HIF1α‐MYCPGC‐1β axis in BRAF V600E thyroid cancer

Abstract: BRAF V600E is the most common mutation identified in thyroid cancers. However, the relationship between BRAF V600E and metabolic reprogramming in thyroid cancer is unclear. Here, we investigate the mechanism of metabolic reprogramming in BRAF V600E thyroid cancer by constructing BRAF V600E‐overexpressing and BRAF‐knockdown thyroid cell lines for use in mitochondrial respiration and glycolysis experiments. Western blot and RT‐qPCR were performed to measure the level of metabolism‐related proteins, and various a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…LDHA catalyses the last step in aerobic glycolysis and is primarily located in muscle tissue, and APRT is an enzyme involved in the adenine nucleotide metabolism [32]. Furthermore, LDHA overexpression has been found in BRAF V600E-mutated thyroid cancer and inactivation of this protein can make cells more sensitive to radiation [38,39]. TGM3 is involved in the transformation of the cell envelope in epidermis and hair follicles, but it is also a tumour suppressor and has been proposed as a progression marker for radio-chemotherapy of head and neck cancers [32,40].…”
Section: Diseases or Functions Annotationmentioning
confidence: 99%
“…LDHA catalyses the last step in aerobic glycolysis and is primarily located in muscle tissue, and APRT is an enzyme involved in the adenine nucleotide metabolism [32]. Furthermore, LDHA overexpression has been found in BRAF V600E-mutated thyroid cancer and inactivation of this protein can make cells more sensitive to radiation [38,39]. TGM3 is involved in the transformation of the cell envelope in epidermis and hair follicles, but it is also a tumour suppressor and has been proposed as a progression marker for radio-chemotherapy of head and neck cancers [32,40].…”
Section: Diseases or Functions Annotationmentioning
confidence: 99%
“…Furthermore, it has also been observed that malignant thyroid lesions have lower citrate levels than benign ones [34,35], as also demonstrated in our results. Studies of in-vitro cultured cells suggest that oncogenic activation of BRAF (often mutated in thyroid cancer) inhibits OXPHOS in mitochondria and promotes aerobic glycolysis to sustain cancer cell growth [36]. Our findings, for the first time, hypothesize a connection between oxidative stress and the alteration of the metabolic profile in thyroid tumors.…”
Section: Discussionmentioning
confidence: 50%
“…PGC-1β regulates mitochondrial biogenesis and oxidative phosphorylation (OXPHOS). Moreover, MEK inhibitor increased OXPHOS-related genes in BRAF p.V600E mutated cell lines [189]. These findings suggest that oncogenic activation of BRAF inhibits OXPHOS in mitochondria and promotes aerobic glycolysis to sustain cancer cell growth.…”
Section: Metabolic Reprogramming In Thyroid Cancermentioning
confidence: 77%